2011
DOI: 10.1089/vbz.2009.0208
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Traditionally Used Western Ghats Plants from India and Their Interactions with Chloroquine Against Chloroquine-Tolerant Plasmodium berghei

Abstract: An ethnopharmacological investigation was undertaken on Western Ghats plants traditionally used to treat malaria; 50 plants were very carefully selected from total of 372 plants, and 216 extracts were prepared and tested for in vivo antiplasmodial activity alone and in combination with chloroquine (CQ) against CQ-tolerant Plasmodium berghei (strain NK65). In in vivo antiplasmodial activity when plant extract alone is used, 81 extracts (or 37.5%) gave 52.90% significant parasitemia inhibition on day 4 postinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In addition to the in vitro efficacy, our in vivo results also showed VOCA to be active in reducing malarial parasitemia levels, as 48.9% suppression at 10 mg kg -1 and >74% at 100 and 200 mg kg -1 are above the threshold of 40% parasite suppression in vivo proposed for a compound to be considered active (Coutinho et al 2013;Rezende et al 2013). Samy and Kadarkari (2011) evaluated the antimalarial potential of extracts from C. rotundus leaves from western India, alone or in combination with chloroquine, against P. berghei tolerant to chloroquine (NK65 strain). Mice treated with a dose of 500 mg kg -1 of crude extract (CE), methanolic extract (ME) and the cyclohexane (CH) and methylene chloride (MC) fractions showed 84, 87, 85 and 80% parasitemia inhibition, respectively.…”
Section: Acta Amazonicasupporting
confidence: 59%
“…In addition to the in vitro efficacy, our in vivo results also showed VOCA to be active in reducing malarial parasitemia levels, as 48.9% suppression at 10 mg kg -1 and >74% at 100 and 200 mg kg -1 are above the threshold of 40% parasite suppression in vivo proposed for a compound to be considered active (Coutinho et al 2013;Rezende et al 2013). Samy and Kadarkari (2011) evaluated the antimalarial potential of extracts from C. rotundus leaves from western India, alone or in combination with chloroquine, against P. berghei tolerant to chloroquine (NK65 strain). Mice treated with a dose of 500 mg kg -1 of crude extract (CE), methanolic extract (ME) and the cyclohexane (CH) and methylene chloride (MC) fractions showed 84, 87, 85 and 80% parasitemia inhibition, respectively.…”
Section: Acta Amazonicasupporting
confidence: 59%
“…In another study, 200 mg/kg of R. serpentina leaf ethanol extract showed antimalarial activity in P. berghei NK65 strain infected mice model with 84.14% chemo suppression, while 400 mg/kg R. serpentina leaf hot water extract showed 82.53% chemo suppression (Omoya et al, 2019). In another in vivo study, a dose of 500 mg/kg of cyclohexane and methylene chloride extracts of R. serpentina root displayed moderate antiplasmodial activity against chloroquine-resistant P. berghei NK65 strain with 20% survival on 9 th day of post-infection (Samy and Kadarkari, 2011).…”
Section: Apocynaceaementioning
confidence: 95%
“…Suppression at the combined doses (20 and 10 mg/kg) ranged from 70 to 95.98% in suppressive, prophylactics and curative tests [5]. Moderate to high in vivo antimalarial activity [30] 11 Carica papaya leaf (50 mg/kg) ART (15 mg/kg) Antagonism [31] Vernonia amygdalina (VA); Artesunate (ART); Plasmodium berghei (P.berghei); Chloroquine (CQ).↓ (Decreased activity), ↑ (Increased activity) Enhanced antiplasmodial activity and mean survival time [11] Vernonia amygdalina (VA); Artesunate (ART); Plasmodium berghei (P. berghei); Chloroquine (CQ). Amodiaquine (AQ).…”
Section: Synopsis Of Studies On Herbal-antimalarial Drugs Interactionmentioning
confidence: 99%
“…A total of 216 extracts from 50 Western Ghats traditionally used to treat malaria were tested for in vivo antiplasmodial activity alone as well as in combination with CQ against CQ-tolerant P. berghei strain. The study revealed that more than 70% of the plant extracts displayed moderate to high in-vivo antimalarial activity when used separately as well as in combination with CQ [30].…”
Section: Synopsis Of Studies On Herbal-antimalarial Drugs Interactionmentioning
confidence: 99%